2019
DOI: 10.1002/jcla.22918
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA expression profile of bovine placentas in late gestation with aberrant SCNT fetus

Abstract: BackgroundsOne of the limitations of somatic cell nuclear transfer (SCNT) strategy to generate genetically modified offspring is the low birth rate. Placental dysfunction is one of the causes of abortion. Circular RNA (circRNA) is noncoding RNA which functions as microRNA (miRNA) sponges in biological processes.MethodsTwo aberrant pregnant placenta (aberrant group, AG) and three normal pregnant placenta (normal group, NG) during late gestation (180‐210 days) with bovine SCNT fetus were collected for high‐throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Increasing evidence suggests that circRNAs could serve as developmental biomarkers and may act as proliferation, differentiation or apoptosis regulators in the animal cell . Recently, circRNAs have been reported to act as sponges for miRNAs and proteins in the cytoplasm for biological regulation and also in the nucleus for regulation of gene expression, with some circRNAs functioning as translation templates and as scaffolds for circRNA–protein complexes . Ju et al found that the main function of circRNAs is to act as “sponges” to absorb miRNAs, thus providing positive control of downstream proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that circRNAs could serve as developmental biomarkers and may act as proliferation, differentiation or apoptosis regulators in the animal cell . Recently, circRNAs have been reported to act as sponges for miRNAs and proteins in the cytoplasm for biological regulation and also in the nucleus for regulation of gene expression, with some circRNAs functioning as translation templates and as scaffolds for circRNA–protein complexes . Ju et al found that the main function of circRNAs is to act as “sponges” to absorb miRNAs, thus providing positive control of downstream proteins.…”
Section: Discussionmentioning
confidence: 99%
“…To further dissect the potential DE circRNA functions in AVF dysfunction development and progression, the miRNA-binding sites of four DE circRNAs (hsa_circ_015036, hsa_circ_005718, hsa_circ_017814, and hsa_circ_007293) were predicted via using miRanda software, which were validated by qRT-PCR. A perfect seed matching between miRNA and target circRNA was considered for a MiRanda score of 140 or higher [14]. The interaction network between the four candidate circRNAs and their corresponding target miRNAs was constructed using Cytoscape 3.6.1.…”
Section: Target Mirna Prediction and Co-expression Network Establishmentmentioning
confidence: 99%
“…We further predicted miRNA binding sites on four candidate circRNAs (hsa_circ_015036, hsa_circ_005718, hsa_circ_017814, and hsa_circ_007293) through miRanda software, which included three downregulated circRNAs and one upregulated circRNA. Based on the criteria of max score ≥ 140 and max energy ≤ -25 [14], a total of 134 miRNA were paired with four DE circRNAs after discarding the repeated values. For each candidate circRNA, top 10 target miRNAs with the highest degree of correlation were considered (a lower max energy is indicative of a stronger correlation) [14], then we acquired 38 miRNAs after discarding repeating target miRNAs.…”
Section: Establishing Interaction Network Between Target Mirnas and Candidate Circrnasmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the advent of next-generation, high-throughput technology has led to the identification of specific functional noncoding RNAs (ncRNAs) with roles in biological development and/or physiological responses [ 9 , 10 , 11 ]. Several studies have suggested that ncRNAs including microRNA (miRNAs), long noncoding RNA (lncRNAs), and circular RNA (circRNAs) play crucial roles in various biological processes in domestic animals [ 12 , 13 , 14 ]. Moreover, some studies have provided evidence supporting that lncRNA/circRNA–miRNA–messenger RNA (mRNA) interactions are important mechanisms underlying mammalian physiological development and diseases [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%